A Comparison of Three Opportunity-to-Respond Strategies on the Academic Engaged Time Among High School Students Who Present Challenging Behavior. (February 2017) - Adamson, Reesha M.; Lewis, Timothy J.
A single subject alternating treatment design across three student-teacher dyads was used to investigate the comparative impact on student academic engaged time of three opportunity-to-respond (OTR) strategies: guided notes, class-wide peer tutoring, and response cards. Participants were three high school students with disabilities with noted behavioral concerns and poor academic performance within mathematics general education courses. Results indicated all OTR interventions were effective in improving percentage of academic engaged time and reducing behavioral disruptions. Using visual analysis and an additional replication phase, response cards proved to the most efficacious in improving student outcomes. Implications for the existing knowledge base on the efficacy of OTR as well as future research within high school settings are discussed.